2010
DOI: 10.3758/brm.42.1.318
|View full text |Cite
|
Sign up to set email alerts
|

Inducing changes in arousal and valence: Comparison of two mood induction procedures

Abstract: This research examined the relative effectiveness of two mood induction procedures (MIPs) for inducing four specific moods varying along the dimensions of both valence and arousal. Participants were randomly assigned either to an autobiographical recall or to a music and guided imagery MIP and underwent a happiness, serenity, anger, or sadness mood induction. The findings confirmed the effectiveness of the two MIPs in producing changes on both the valence and arousal dimensions of mood. The results also reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
89
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(99 citation statements)
references
References 45 publications
(61 reference statements)
7
89
0
3
Order By: Relevance
“…Usually, participants have to recollect the event as vividly as possible, relieving and reexperiencing the emotions, sensations, perceptions, and reactions (Westermann et al, 1996). This procedure can be used alone or combined with other mood induction procedures (Jallais & Gilet, 2010). Studies comparing different mood induction procedures have demonstrated the greater effectiveness of autobiographical recall relative to other approaches (Gilet, 2008;Jallais & Gilet, 2010;Zhang, Yu, & Barrett, 2014), especially when it is used to induce positive emotions (Strack, Schwarz, & Gschneidinger, 1985).…”
Section: Autobiographical Recall As a Mood Induction Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Usually, participants have to recollect the event as vividly as possible, relieving and reexperiencing the emotions, sensations, perceptions, and reactions (Westermann et al, 1996). This procedure can be used alone or combined with other mood induction procedures (Jallais & Gilet, 2010). Studies comparing different mood induction procedures have demonstrated the greater effectiveness of autobiographical recall relative to other approaches (Gilet, 2008;Jallais & Gilet, 2010;Zhang, Yu, & Barrett, 2014), especially when it is used to induce positive emotions (Strack, Schwarz, & Gschneidinger, 1985).…”
Section: Autobiographical Recall As a Mood Induction Proceduresmentioning
confidence: 99%
“…More recently, neuroimaging techniques have also been used to investigate the neural correlates of affective phenomena and emotions, including happiness (for reviews, see Phan, Wager, Taylor, & Liberzon, 2002;Vytal & Hamann, 2010). This area of research requires mood induction procedures (see Westermann, Spies, Stahl, & Hesse, 1996, for a review), and one of the most effective is autobiographical recall (Baker & Gutterfreund, 1993;Jallais & Gilet, 2010).…”
mentioning
confidence: 99%
“…In any event, an anxiety induction procedure that consists of reading Velten self-statements plus listening to anxiogenic music followed by a short incubation period seems to be a valid procedure for most adults, independently of their age. This procedure would be a successful combination and would imply a first induction that occupies foreground attention and a second one that contributes to a congruent background atmosphere (Jallais & Gilet, 2010). There are some general problems inherent to the use of experimental mood induction procedures.…”
Section: Discussionmentioning
confidence: 99%
“…The effects on mood induction by listening to music were compared to the effects obtained via autobiographical memories [28].…”
Section: Emotional Effects Of (Known) Musical Piecesmentioning
confidence: 99%